Globalisation Impacts
XVI, 193 p. 11 illus., 9 illus. in color.
Keywords: The book reviews globalisation by identifying causes behind the discontent it has produced in recent years. It variously engages in economics, political economy, development and policy discourses to study experiences of countries and institutions in managing and adjusting to globalisation. Extending the analysis to latest global developments, including the remarkable advance of technology and digitalisation, and political and economic upheavals caused by COVID19, the book collects varied academic perspectives and reflects on the present as well as future. Comprising chapters written by distinguished academics and policy experts, the book is a rare collection of cross-disciplinary objective evaluations of globalisation.